The Noteworthiness of Meteion’s Will to Power in Naoki Yoshida’s Final Fantasy XIV: Endwalker - Annasai, Axlinabila Annisa; Pasopati, Rommel Utungga; Wijaya, Kusuma; Hariyono, Hariyono; Kartiningsih, Rindrah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This paper examines how Meteion’s Will to Power, a concept central to Friedrich Nietzsche’s philosophy, is manifested within the narrative of Final Fantasy XIV: Endwalker. Meteion is a character from the game Final Fantasy XIV: Endwalker, created by a scientist named Hermes. She and her sisters, known as the Meteia, were made to find the purpose of life but ended up wanting to destroy all existence after seeing too much destruction. Then, how is Meteion’s Will to Power reflected in Final Fantasy XIV: Endwalker? Through qualitative method in explorative approach, this study analyzes the relationship between Meteion’s actions and Nietzschean nihilism, where the disintegration of values leads to a perception of life as meaningless. Nietzsche’s perspective posits the will to power as the primary driving force in humans, emphasizing self-determination and the exertion of one’s will on the environment. Meteion’s journey, marked by despair and a wish to end all suffering, shows how Nietzsche’s idea of the Will to Power can lead to nihilism, moving from a passive to an active form. In conclusion, Meteion’s actions highlight Nietzsche’s belief that overcoming nihilism needs a reevaluation of values, showing the Will to Power’s role in facing existential despair.